Is your mama a llama? [videorecording (DVD)] : --and more classic children's stories - Madigan, Amy; Hurt, Mary Beth; Allen, Buffy; Maxwell, Roberta, 1942-; Guarino, Deborah; Wells, Rosemary; Ahlberg, Janet; Ahlberg, Allan; Galdone, Paul; Wells, Rosemary (Scholastic storybook treasures., 2011)
Is your mama a llama?: Through playful rhyme and riddle, a young llama learns about different kinds of animals; Noisy Nora: What's a wee mouse to do when little brother and big sister take up all of mom and dad's time? Make noise!; Each peach pear plum: Children play 'I spy' with favorite nursery rhyme characters in this beloved story; The little red hen: The classic tale of a hardworking hen who teaches her friends a thing or two about helping out; Reading to your bunny: An original story by Rosemary Wells that highlights the importance of reading to children.